The Role of Islamic Microfinance Institutions in Promoting UMKM (Micro, Small, and Medium Enterprises) Growth in Indonesia: A SWOT Analysis - Susiati; Wargo; Kuswanto (Zabags Qu Publish, 2025)
This study investigates the role of Islamic microfinance institutions in fostering the growth of UMKM (Micro, Small, and Medium Enterprises) in Indonesia by applying a SWOT (Strengths, Weaknesses, Opportunities, Threats) framework. Motivated by the gap between the considerable potential of Islamic microfinance as an inclusive financial instrument and persistent implementation challenges such as limited financial literacy, restricted outreach, and regulatory fragmentation the research aims to map internal and external strategic factors that affect institutional effectiveness. Employing a qualitative descriptive-analytic approach, data were collected through in-depth interviews, field observation, institutional documentation, and review of relevant policy and literature. Findings reveal that core strengths include profit-and-loss sharing mechanisms and social commitment, while key weaknesses comprise low Islamic financial literacy among UMKM actors and constrained service coverage. Identified opportunities center on digitalization and supportive pro-Islamic finance regulations; principal threats include strong competition from conventional finance providers and uneven regulatory implementation. The study concludes that realizing the strategic potential of Islamic microfinance requires integrated actions digital innovation, literacy enhancement, and institutional coordination to advance inclusive and sustainable economic empowerment for UMKM in Indonesia.